Intercultural awareness and its misrepresentation in textbooks - Henao Mejía, Edwin Alejandro; Gómez Salazar, José Orlando; Murcia Yalí, Jorge Heriberto (Colombian Applied Linguistics Journal, 2019)
The role of culture and intercultural awareness in the language classroom is not a new area of research in ESL/EFL, and its relative importance has shifted in different approaches and methods of foreign language teaching. Today, the goal of some English textbooks has transcended a pure linguistic and language training orientation as text developers have moved towards also teaching intercultural awareness. The development of intercultural awareness was presented as a key component in ensuring the success of the latest Colombian National Bilingual Programme 2015-2025 (NBP), and the textbook series English, Please! was promoted as a breakthrough in this context. This article presents the research analysis and findings of an exploratory study based on the ambitious task set forth in the NBP policy on English textbooks. We examine the theoretical constructs adopted by the National Ministry of Education and by using, both quantitative and qualitative, analysis we explore the intercultural awareness activities presented in the series. At the end, we suggest that although the series is an important addition to existing materials in the area, it presents an overly reductionist and instrumentalist use of the concept of intercultural awareness.